2016
DOI: 10.1051/0004-6361/201526818
|View full text |Cite
|
Sign up to set email alerts
|

The XXL Survey

Abstract: We present 2.1 GHz imaging with the Australia Telescope Compact Array (ATCA) of a 6.5 deg 2 region within the XXM-Newton XXL South field using a band of 1.1−3.1 GHz. We achieve an angular resolution of 4.7 × 4.2 in the final radio continuum map with a median rms noise level of 50 µJy/beam. We identify 1389 radio sources in the field with peak S /N ≥ 5 and present the catalogue of observed parameters. We find that 305 sources are resolved, of which 77 consist of multiple radio components. These number counts ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…also Padovani et al 2015) is noticeable. In addition, the total counts (black) are in remarkable agreement with the observations by Prandoni et al (2017), Smolcic et al (2016) and Vernstrom et al (2016). We stress that at around S ∼ 0.5 mJy, a fraction of 1% of the counts is contributed by strongly, lensed high-redshift SFGs, whose identification by followup observations will be extremely important.…”
Section: Resultssupporting
confidence: 90%
“…also Padovani et al 2015) is noticeable. In addition, the total counts (black) are in remarkable agreement with the observations by Prandoni et al (2017), Smolcic et al (2016) and Vernstrom et al (2016). We stress that at around S ∼ 0.5 mJy, a fraction of 1% of the counts is contributed by strongly, lensed high-redshift SFGs, whose identification by followup observations will be extremely important.…”
Section: Resultssupporting
confidence: 90%
“…The two fields have an extensive multiwavelength coverage from X-ray to radio wavelengths (the detailed descriptions are given in XXL Paper I and Fotopoulou et al 2016, hereafter XXL Paper VI 1 ). Baran et al (2016; hereafter XXL Paper IX) and Smolčić et al (2016; hereafter XXL Paper XI) presented radio observations of XXL with the Very Large Array (VLA) and the Australia Telescope Compact Array (ATCA), respectively. Butler et al (2018a, hereafter XXL Paper XVIII) reported the new observations of the full XXL-S with ATCA.…”
Section: The Xxl Survey and The Samplementioning
confidence: 99%
“…For XLSSC 634 in XXL-S, the image was taken from the BCS survey (Desai et al 2012) with the Mosaic2 imager on the Blanco 4 m telescope 5 . For radio data we used the NRAO VLA Sky Survey (Condon et al 1998) and Tasse et al (2008) for the XXL-N field and used Australia Telescope Compact Array (ATCA) data (Smolčić et al 2016 -also known as XXL Paper XI; Butler et al 2018 -also known as XXL Paper XVIII) for the XXL-S field (for XLSSC 634). We define an optical or radio source as a likely counterpart to a Chandra detected point source if it falls within 2 of the Chandra detected point source coordinates.…”
Section: Point Source Detection and Flux Calculationmentioning
confidence: 99%